2022
DOI: 10.3389/fmicb.2022.982152
|View full text |Cite
|
Sign up to set email alerts
|

Alginate oligosaccharides increase boar semen quality by affecting gut microbiota and metabolites in blood and sperm

Abstract: Alginate oligosaccharides (AOS), natural polymers from brown seaweeds (such as Laminaria japonica, Undaria pinnatifida, and Sargassum fusiforme), have been reported to possess many beneficial advantages for health. In the current study, after 9 weeks of dietary supplementation, AOS 10 mg/kg group (AOS 10) group increased boar sperm motility from 87.8% to 93.5%, p < 0.05. Moreover, AOS10 increased the relative abundances of Bifidobacterium, Coprococcus, Butyricicoccus (1.3–2.3-fold; p < 0.05) to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Sperm metabolites play a vital role in the procedure of spermatogenesis ( Zhao et al., 2022 ). Studies have shown that AOS was conducive to improving the blood metabolome of boars, which, in turn, affects systemic metabolism ( Han et al., 2022 ; Hao et al., 2022 ). At the same time, AOS was also conducive to improving metabolites in boar sperm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sperm metabolites play a vital role in the procedure of spermatogenesis ( Zhao et al., 2022 ). Studies have shown that AOS was conducive to improving the blood metabolome of boars, which, in turn, affects systemic metabolism ( Han et al., 2022 ; Hao et al., 2022 ). At the same time, AOS was also conducive to improving metabolites in boar sperm.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, AOS was also conducive to improving metabolites in boar sperm. In the experiment involving young boars, AOS could improve some unsaturated fatty acids, amino acids, and antioxidants to improve semen quality ( Han et al., 2022 ). In this study, AOS improved the sperm metabolome of aging boars; several types of fatty acids and derivatives were significantly increased, such as butyrylcarnitine, propionylcarnitine, and adrenic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alginate oligosaccharides are dietary supplements that improve the GM composition, boost beneficial metabolites in serum and semen, and have long-term advantages for enhancing boar semen quality. 17 However, enteric dysbacteriosis resulting from ingested poisons, such as bisphenol-A or organophosphorus pesticides, may exacerbate reproductive toxicity and have an adverse impact on the semen quality. 18,19 Researchers are exploring the connection between the GM and reproductive parameters, and the gut-testis axis concept 20 provides new insights into the mechanism underlying the relationship between Se and the semen quality.…”
Section: Introductionmentioning
confidence: 99%
“…coli , and increased the SCFA (e.g., acetic acid and butyric acid) and lactic acid contents. As an animal dietary additive, AOS also increased the relative abundance of Bifidobacterium , Coprococcus , and Butyricicoccus (Han et al 2022 ). However, the complex mechanisms involved in the metabolic changes caused by AOS and the mechanisms underlying its antibacterial activity in the intestine remain unclear.…”
Section: Introductionmentioning
confidence: 99%